Virus-derived gene transfer agents benefit host cells by providing templates for DNA repair - Lang, Andrew S. (PLoS biology, 2022)
The potential benefits of producing gene transfer agents (GTAs) have long been speculated. A new study in PLOS Biology shows that DNA transfer by these phage-like elements allows cells with DNA damage to perform DNA repair and survive.